Investigation of shaded atrium building in hot and humid climate - Aram, Reihaneh; Alibaba, Halil Zafer (American Institute of Physics Inc., 2023)
Reaching the maximum level of the users' comfort in the building is an important role. At the same time, it is vital to have occurred minimum negative environmental effects. Having an atrium as a popular area in the building needs to investigate thermal performance. This paper finds out the effects of the floor heigh into the internal condition as the liner atrium with optimum shading device during the warm period. This paper illustrated the different results according to the atrium building height as floor numbers including 1, 3, and 5 floors in Famagusta, North Cyprus climate. As finding in all building height simulation models in August is the maximum discomfort condition month and maximum cooling loads as air-conditioning system, because of internal building gained and ventilation gains, (single floor Qz between 330 to-330 watts, Qv:-2000 to 2000 watts), (three floors Qz between 1200, 2200 watts to-1200,-2200 watts, Qv:-7000 to 7000 watts), and (five floors Qz between 2000, 4500 watts to-2000,-4500 watts, Qv:-12000 to 12000 watts) however, the optimum shading device as 35% over the south external facade of atrium applied but the fully air-conditioned is necessary especially from morning to afternoon time. It found that, while the floor height of the total building and atrium height increased, heat transferring massively occurred during morning time especially as passive performance. © 2023 Author(s).
7th World Multidisciplinary Civil Engineering-Architecture-Urban Planning Symposium, WMCAUS 2022 -- 2022-09-05 through 2022-09-09 -- Prague -- 193356